2012
DOI: 10.1108/jpbafm-24-03-2012-b002
|View full text |Cite
|
Sign up to set email alerts
|

Citizen perceptions of general-purpose and special district governments: A comparative analysis

Abstract: Special districts comprise over 40% of local governments, prompting debate on the merits of general versus special entities. Previous research focused on relative cost-efficiency and tended to ignore how special districts impact government accountability. This study fills a critical need by testing how type of government (general versus special) impacts citizen awareness of and familiarity with government, a precondition for accountability. Drawing from two theoretical perspectives (institutional reform and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Under the revenue‐complexity hypothesis, as special districts proliferate and the local government landscape becomes more complex, it is increasingly difficult for taxpayers to identify the tax price for local public goods and thus, public expenditures and associated debt will be higher. Consistent with this hypothesis, Killian and Le () find that citizens are less familiar with the role and functions of special district government than that of general purpose governments. Debt illusion occurs when debt‐financed projects have a lower perceived tax price than current tax payments so that households demand higher levels of local government expenditures through debt financing.…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…Under the revenue‐complexity hypothesis, as special districts proliferate and the local government landscape becomes more complex, it is increasingly difficult for taxpayers to identify the tax price for local public goods and thus, public expenditures and associated debt will be higher. Consistent with this hypothesis, Killian and Le () find that citizens are less familiar with the role and functions of special district government than that of general purpose governments. Debt illusion occurs when debt‐financed projects have a lower perceived tax price than current tax payments so that households demand higher levels of local government expenditures through debt financing.…”
Section: Literature Reviewmentioning
confidence: 90%
“…As such, they contribute to citizen confusion as well as financial risk. Previous research has shown that citizens are less aware of the existence of special districts and less able to hold them accountable for programs, operations, and financial practices (Killian and Le ). This research shows that an increase in the number of special districts is associated with an increase in local debt in some states.…”
Section: Discussionmentioning
confidence: 99%
“…First, the city and county government authorities are originally responsible for the jurisdiction-wide, all-inclusive public service provision when the special districts did not exist. Second, citizens tend to be su ciently aware to hold the general-purpose governments accountable for public service provisions but tend to be rather naïve about how to hold special districts accountable (Killian & Le, 2012). Third, if the public service responsibilities were not externalized to special districts, all constituent citizens would bene t from the service provisions of the general-purpose governments, regardless of income level and residential location.…”
Section: Service Accountability and Missing Cost Behind Specialized S...mentioning
confidence: 99%
“…The results indicate that a greater number of special districts tends to decrease the quality of nancial conditions of general-purpose governments.Findings of this study add to the current knowledge of special districts and their scal impacts. General-purpose governments may externalize some service responsibility to special districts, but adverse social impacts from these 'shadow governments' remain billed to general-purpose governments that are more awarable to citizens (Killian & Le, 2012; Judd, McKenzie, & Alexander, 2021). In the following sections, this study brie y reviews the determinants of local nancial conditions, with a speci c focus on intergovernmental relationships.…”
mentioning
confidence: 99%
“…Opponents of special districts view them as opaque, challenging for residents to hold accountable, and susceptible to capture by special interests. Bollen (1957) famously called special districts "shadow governments," and this general view has been echoed by numerous scholars since (Killian and Le 2012;Burns 1994). Empirical research has shown that special districts may indeed by less visible, with Killian and Le (2012) finding that residents are less likely to be aware of special districts than general purpose governments.…”
mentioning
confidence: 99%